Computational design of fusion proteins against ErbB2-amplified tumors inspired by ricin toxin - Ahmadi Moghaddam, Yasser; Maroufi, Asad; Zareei, Sara; Irani, Mehdi (Frontiers in Molecular Biosciences, 2023)
Although the anti-cancer activity of ricin is well-known, its non-specific targeting challenges the development of ricin-derived medicines. In the present study, novel potential ribosome-inactivating fusion proteins (RIPs) were computationally engineered by incorporation of an ErbB2-dependant penetrating peptide (KCCYSL, MARAKE, WYSWLL, MARSGL, MSRTMS, and WYAWML), a linker (either EAAAK or GGGGS) and chain A of ricin which is responsible for the ribosome inactivation. Molecular dynamics simulations assisted in making sure that the least change is made in conformation and dynamic behavior of ricin chain A in selected chimeric protein (CP). Moreover, the potential affinity of the selected CPs against the ligand-uptaking ErbB2 domain was explored by molecular docking. The results showed that two CPs (CP2 and 10) could bind the receptor with the greatest affinity.